PENINGKATAN KETERAMPILAN BERKOMUNIKASI BAHASA MANDARIN MELALUI PERMAINAN INTERAKTIF UNTUK MEMPERSIAPKAN TENAGA KERJA SIAP PAKAI (STUDI EKSPERIMEN PADA SISWA SMAIT AL-ICHWAN CIKARANG UTARA) - Herdiansyah, Haris; Adji, Riyanto (Universitas Nusantara PGRI Kediri, 2022)
In the current industrial era, the People's Republic of China is a country that is very aggressively expanding in many industrial fields. This condition has resulted in the opening of many job opportunities for prospective employees, especially those from vocational-based schools such as vocational high schools in companies of the People's Republic of China or those in partnership with the People's Republic of China. However, the high demand for prospective workers requires prospective employees to have special skills, namely communication skills using the Mandarin language. This study aims to see the effect of interactive games, namely guessing words, making sentences, and competing quickly on improving the social skills of students at the Al Ichwan Cikarang Integrated Islamic High School in Bekasi district. This research is quantitative research with experimental method using pre-test post-test control group design, which will be applied to the research subjects as many as fifty students (n=50). The research instrument is the Chinese Language Skills Scale consisting of 39 question items using the Likert model answer choices with five answer options (Strongly Agree, Agree, Neutral, Disagree, Strongly Disagree). Test the validity and reliability of the scale using Pearson and Cronbach's Alpha, classical assumption test using normality test, heteroscedasticity test, multicollinearity test, while hypothesis testing using multiple regression test. The alternative hypothesis (Ha) in this study is